The Polyanalgesic Consensus Conference (PACC): Recommendations on Intrathecal Drug Infusion Systems Best Practices and Guidelines. Issue 2 (2nd January 2017) - Deer, Timothy R.; Pope, Jason E.; Hayek, Salim M.; Bux, Anjum; Buchser, Eric; Eldabe, Sam; De Andrés, Jose A.; Erdek, Michael; Patin, Dennis; Grider, Jay S.; Doleys, Daniel M.; Jacobs, Marilyn S.; et al.
Abstract : Introduction: Pain treatment is best performed when a patient‐centric, safety‐based philosophy is used to determine an algorithmic process to guide care. Since 2007, the International Neuromodulation Society has organized a group of experts to evaluate evidence and create a Polyanalgesic Consensus Conference (PACC) to guide practice. Methods: The current PACC update was designed to address the deficiencies and innovations emerging since the previous PACC publication of 2012. An extensive literature search identified publications between January 15, 2007 and November 22, 2015 and authors contributed additional relevant sources. After reviewing the literature, the panel convened to determine evidence levels and degrees of recommendations for intrathecal therapy. This meeting served as the basis for consensus development, which was ranked as strong, moderate or weak. Algorithms were developed for intrathecal medication choices to treat nociceptive and neuropathic pain for patients with cancer, terminal illness, and noncancer pain, with either localized or diffuse pain. Results: The PACC has developed an algorithmic process for several aspects of intrathecal drug delivery to promote safe and efficacious evidence‐based care. Consensus opinion, based on expertise, was used to fill gaps in evidence. Thirty‐one consensus points emerged from the panel considerations. Conclusion: New algorithms and guidance have been established to improve care with the use of intrathecal drug delivery.